PELATIHAN KADER GEREJA HIJAU TENTANG GERAKAN GEREJA HIJAU - Kusyanti, Florentina; Lustiyati, Elisabeth Deta (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2023)
In today's world, with the rapid increase in technology, and many people who are less concerned with the natural world, there will be a change in the world's climate, including in Indonesia. So, together with the laudatosi from Rome, the church in Indonesia held a green church movement which aims to reduce heat, so that Crowded churches are the catalyst for the green movement to block global warming. The purpose of this counseling is to mobilize Catholics in the Kedu Kevikepan area which consists of 13 parishes, 1 parish co-op and 2 special administrative parishes to hold a seminar with the theme of the Green Church Movement, so that parishioners will love the environment so that the earth will take sorting action, prevent and treat. The expected results after the participants attend this seminar will be to implement the Green Church Movement in their respective parishes.